The Future of Liberation Theologies: Rumours of Their Demise Have Been Greatly Exaggerated - Medina, Néstor (Toronto journal of theology, 2007)
An expatriate returning to Latin America after two decades abroad would be struck by the dramatic changes in many aspects of life there, including religion. Many of these changes stem from the development of "free" market capitalism, the ambiguous nature and uneven character of which have become obvious.